The Influence of the Board of Commissioners and Institutional Ownership on the Financial Performance of Mining Companies on the IDX in 2018-2020 - I Dewa Nyoman Badera; Kusuma dewi, Putri (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to examine the effect of the Board of Commissioners and Institutional Ownership on the Company's Financial Performance as proxied by using Return on Assets (ROA). This research was conducted on mining companies listed on the Indonesia Stock Exchange in 2018-2020. The sample used as many as 12 companies with a total sample of 36 observations in 3 years. The data analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that the Board of Commissioners and Institutional Ownership have a positive effect on the company's financial performance. With the number of boards of commissioners and increasing institutional ownership can increase supervision which can make the company's financial performance increase.